2008
DOI: 10.1111/j.1740-0929.2007.00500.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of fattening performance in Brahman grade cattle (Bos indicus) and crossbred water buffalo (Bubalus bubalis) fed on high roughage diet

Abstract: The objective of this study was to compare the fattening performance in Brahman grade cattle (crossbred cattle) and crossbred water buffalo at the same young age and fed with high roughage based fattening rations in the Philippines. Ten crossbred cattle and 10 crossbred water buffalo, aged between 18 and 24 months old were used in this experiment. The animals were fed diets consisting of 85% Napier or Para grass and 15% concentrate mixture (CM) on a dry matter (DM) basis. The grass, total DM intake and bodywei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 11 publications
3
19
0
Order By: Relevance
“…This showed that mithun had higher intake of nutrients than Tho-tho cattle, and higher intake of nutrient resulted to increased growth rate in this species of animal. When buffaloes were compared with cattle in many experiments, similar results of higher DM intake in buffaloes than cattle were recorded (Kennedy 1990;Ichinohe et al 2004;Lapitan et al 2008), and higher DM intake is responsible for higher growth rate of animals (Trach and Thom 2004;Lapitan et al 2008). Paul et al (2003) reported that DM intake was significantly lower in buffaloes than cattle.…”
Section: Feed Intakesupporting
confidence: 56%
See 3 more Smart Citations
“…This showed that mithun had higher intake of nutrients than Tho-tho cattle, and higher intake of nutrient resulted to increased growth rate in this species of animal. When buffaloes were compared with cattle in many experiments, similar results of higher DM intake in buffaloes than cattle were recorded (Kennedy 1990;Ichinohe et al 2004;Lapitan et al 2008), and higher DM intake is responsible for higher growth rate of animals (Trach and Thom 2004;Lapitan et al 2008). Paul et al (2003) reported that DM intake was significantly lower in buffaloes than cattle.…”
Section: Feed Intakesupporting
confidence: 56%
“…This was again supported by the fact that the digestibilities of different nutrients were comparable between two species of animals. Some workers reported higher cellulose digestibility in buffaloes than cattle (Wanapat et al 2000;Ichinohe et al 2004), whereas others did not observe any difference (Lapitan et al 2008). In this experiment of comparison between mithun and cattle, no such difference was noticed in the rumen liquor.…”
Section: Rumen Enzyme Profilesmentioning
confidence: 82%
See 2 more Smart Citations
“…Part of this work has been briefly published by Lapitan et al (2008). The diameters of muscles involved in mastication were also measured to associate its development for feeding behavior and nutrient digestibility, supplementing our understanding on better animal performance.…”
Section: Introductionmentioning
confidence: 99%